2011
DOI: 10.4103/0970-9290.87080
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of expression of cell adhesion molecule (CD44) splice variants: CD44 standard (CD44s) and v5, v6 isoforms in oral leukoplakias: An immunohistochemical study

Abstract: Among CD44s and its variant isoforms,v5, v6, in this study, variant isoform v6 may serve as a marker in detecting high-risk leukoplakias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…Moreover, a significant difference was observed in the expression patterns of CD44v6, SYNE1, and miR34a in leukoplakia patients compared to their healthy counterparts, thereby suggestive of the role of these markers in early diagnosis and early risk prediction of OSCC using non‐invasive techniques. Our findings are in concordance with the results of Godge et al; however, they are in sharp contradiction with the work of Chaiyarit et al who found a significant reduction in the expression of CD44v6 in oral leukoplakia patients compared to controls. This discrepancy could be attributed to the difference in sample source and techniques employed.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, a significant difference was observed in the expression patterns of CD44v6, SYNE1, and miR34a in leukoplakia patients compared to their healthy counterparts, thereby suggestive of the role of these markers in early diagnosis and early risk prediction of OSCC using non‐invasive techniques. Our findings are in concordance with the results of Godge et al; however, they are in sharp contradiction with the work of Chaiyarit et al who found a significant reduction in the expression of CD44v6 in oral leukoplakia patients compared to controls. This discrepancy could be attributed to the difference in sample source and techniques employed.…”
Section: Discussionsupporting
confidence: 73%
“…87 In OL, CD44 variant isoform v6 (CD44 v6), but not CD44 standard or CD44 v5, was found to be decreased along with increasing grades of dysplasia. 88 However, Rautava et al 89 reported that CD44 v6 expression did not show a significant correlation with oral dysplasia and its outcome, thus reducing its potential usefulness as a prognostic marker of PPOELs.…”
Section: Cell Adhesion-related Moleculesmentioning
confidence: 99%
“…The CD44 gene represents an interesting example of SAM68-mediated coupling between signal transduction cascades and alternative splicing. CD44 pre-mRNA is affected by complex alternative splicing events occurring in 10 adjacent exons (v1–v10) to produce multifunctional transmembrane glycoprotein isoforms implicated in cell-cell and cell-matrix adhesion, migration, and invasion [ 77 ] and with crucial roles in cancer progression and metastasis [ 78 ]. By binding to A/U-rich enhancer element located within exon v5 , SAM68 promotes the production of the oncogenic CD44v5 variant ( Figure 3(b) , (A)) [ 71 ], which is upregulated in several cancers [ 78 , 79 ] and bears prognostic value in gastric and renal carcinoma [ 80 – 82 ].…”
Section: Sam68-regulated Alternative Splicing Events In Cancermentioning
confidence: 99%